Chemotherapy triggers cachexia by deregulating synergetic function of histone‐modifying enzymes. Issue 1 (10th December 2020) - Amrute‐Nayak, Mamta; Pegoli, Gloria; Holler, Tim; Lopez‐Davila, Alfredo Jesus; Lanzuolo, Chiara; Nayak, Arnab
Abstract: Background: Chemotherapy is the first line of treatment for cancer patients. However, the side effects cause severe muscle atrophy or chemotherapy‐induced cachexia. Previously, the NF‐κB/MuRF1‐dependent pathway was shown to induce chemotherapy‐induced cachexia. We hypothesized that acute collateral toxic effects of chemotherapy on muscles might involve other unknown pathways promoting chemotherapy‐induced muscle atrophy. In this study, we investigated differential effects of chemotherapeutic drugs and probed whether alternative molecular mechanisms lead to cachexia. Methods: We employed mouse satellite stem cell‐derived primary muscle cells and mouse C2C12 progenitor cell‐derived differentiated myotubes as model systems to test the effect of drugs. The widely used chemotherapeutic drugs, such as daunorubicin (Daun), etoposide (Etop), and cytarabine (Ara‐C), were tested. Molecular mechanisms by which drug affects the muscle cell organization at epigenetic, transcriptional, and protein levels were measured by employing chromatin immunoprecipitations, endogenous gene expression profiling, co‐immunoprecipitation, complementation assays, and confocal microscopy. Myotube function was examined using the electrical stimulation of myotubes to monitor contractile ability (excitation–contraction coupling) post drug treatment. Results: Here, we demonstrate that chemotherapeutic drugs disrupt sarcomere organization and thereby the contractile ability of skeletal muscle cells. The sarcomere disorganization results from severe loss of molecular motor protein MyHC‐II upon drug treatment. We identified that drugs impede chromatin targeting of SETD7 histone methyltransferase and disrupt association and synergetic function of SETD7 with p300 histone acetyltransferase. The compromised transcriptional activity of histone methyltransferase and acetyltransferase causes reduced histone acetylation and low occupancy of active RNA polymerase II on MyHC‐II, promoting drastic down‐regulation of MyHC‐II expression ( 3.6‐fold and 4.5‐fold reduction of MyHC‐IId mRNA levels in Daun and Etop treatment, respectively. P < 0.0001). For MyHC‐IIa, gene expression was down‐regulated by 2.6‐fold and 4.5‐fold in Daun and Etop treatment, respectively ( P < 0.0001). Very interestingly, the drugs destabilize SUMO deconjugase SENP3. Reduction in SENP3 protein level leads to deregulation of SETD7–p300 function. Importantly, we identified that SUMO deconjugation independent role of SENP3 regulates SETD7–p300 functional axis. Conclusions: The results show that the drugs critically alter SENP3‐dependent synergistic action of histone‐modifying enzymes in muscle cells. Collectively, we defined a unique epigenetic mechanism targeted by distinct chemotherapeutic drugs, triggering chemotherapy‐induced cachexia.